The Influence of Cristiano Ronaldo's Individual Record Achievements on Sponsor Firms' Abnormal Stock Returns: A Case Study of Nike and Herbalife - Dewa Putu Yohanes Agata L. Sandopart (Lembaga Publikasi Ilmiah Nusantara, 2023)
This study analyzes the influence of Cristiano Ronaldo's individual record achievements on the abnormal stock returns of sponsoring companies, focusing on Nike and Herbalife as case studies. The phenomenon of elite athlete endorsement has become a common practice in corporate marketing strategy; however, the literature remains limited in explaining the mechanism through which positive athletic performance affects shareholder value. This research employs a qualitative approach with a multiple-case study design. Data were collected through in-depth interviews with 12 informants comprising financial analysts, sports marketing experts, and retail investors, as well as document analysis of financial reports, analyst reports, and media coverage from the 2017–2023 period. The findings reveal that Cristiano Ronaldo's individual record achievements exert an asymmetric influence on abnormal stock returns: Nike demonstrates a positive response characterized by increased trading volume and investor sentiment, whereas Herbalife shows no significant response. Four key moderating factors are identified: brand-athlete congruence, investor profile, framing in analyst reports, and macroeconomic context. This study concludes that the effectiveness of athlete endorsement in creating shareholder value is not automatic but depends heavily on the alignment between the athlete's image and the sponsor's brand identity. The theoretical implication extends congruence theory into the domain of behavioral finance, while the practical implication guides corporate management in evaluating endorsement investments.